Development of a Student Character Assessment Monitoring System Based on Microsoft Excel: Rehobot Palangka Raya Junior High School (SMP) Based on Microsof Excel - Sitohang, Hotmian; Rudini, Rudini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Rehobot Palangka Raya Junior High School (SMP) is a Christian school that has a vision to become a center of education and the formation of superior national leaders who are strong in intelligence, faith, and character. Student characteristics are one of the variables of teaching conditions in schools. Student characteristics are one of the variables of teaching conditions in schools. So character is a portrait of a person's good and bad self. A student is not only required to be smart in thinking, but must also be smart in behaving. Therefore, SMP Rehobot has character assessment indicators in the form of order and discipline, responsibility, and growth of faith. So far, the recapitulation of student character determination values ​​has been carried out by teachers writing student values ​​into a recapitulation book. This makes it difficult for schools to determine assessments because assessments are carried out every school day. Using a manual method also makes it difficult for teachers to weight each student's grades. Using manual methods also makes it difficult for teachers to weight each student's grades. The purpose of creating this system is to make it easier for schools to manage behavioral data in the school environment and determine final grades accurately, making it easier for homeroom teachers to know the development of student character. System development uses ERD (Entity Relationship Diagram) and DFD (Data Flow Diagram). This application was developed using Microsoft Excel.